Can a Risk Factor Based Approach Safely Reduce Screening for Retinopathy of Prematurity? - K. M. Friddle; B. A. Yoder; M. E. Hartnett; E. Henry; R. J. DiGeronimo (International Journal of Pediatrics)
Objective. Current American retinopathy of prematurity (ROP) screening guidelines is imprecise for infants ≥ 30 weeks with birth weights between 1500 and 2000 g. Our objective was to evaluate a risk factor based approach for screening premature infants at low risk for severe ROP. Study Design. We performed a 13-year review from Intermountain Health Care (IHC) data. All neonates born at ≤32 weeks were reviewed to determine ROP screening and/or development of severe ROP. Severe ROP was defined by stage ≥ 3 or need for laser therapy. Regression analysis was used to identify significant risk factors for severe ROP. Results. We identified 4607 neonates ≤ 32 weeks gestation. Following exclusion for death, with no retinal exam or incomplete data, 2791 (61%) were included in the study. Overall, severe ROP occurred in 260 (9.3%), but only 11/1601 ≥ 29 weeks (0.7%). All infants with severe ROP ≥ 29 weeks had at least 2 identified ROP risk factors. Implementation of this risk based screening strategy to the IHC population over the timeline of this study would have eliminated screening in 21% (343/1601) of the screened population. Conclusions. Limiting ROP screening for infants ≥ 29 and ≤ 32 weeks to only those with clinical risk factors could significantly reduce screening exams while identifying all infants with severe ROP.